2018
DOI: 10.1186/s12929-018-0472-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant in CXCL12 gene raises susceptibility to HPV infection and squamous intraepithelial lesions development: a case-control study

Abstract: BackgroundHuman papillomavirus (HPV) is the most common sexually transmitted virus in women worldwide. The persistence of the virus may cause warts that are considered benign lesions and low or high grade intraepithelial lesions (LSIL/HSIL). Immunological system plays an important role in the resolution of infections. In this context, we highlight the chemokines, which are important regulators in the development of viral infections and inflammation. Among which CXCL12 stands out, due to its pro-inflammatory fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…Corsten et al found that CVB3 infection promoted the miR-221/-222 expression in cardiac tissue. Further study demonstrated that miR-221/-222 could inhibit ETS1/2, interferon regulatory factor 2 (IRF2), Bcl-2-like protein 11 (BCL2L11), Thymocyte selection-associated high-mobility group box (TOX), BCL-2-modifying factor (BMF), and CXC chemokine ligand 12 (CXCL12) As we all know, those target genes are important in viral replication and inflammation (Welsh, 1986 ; Bosselut et al, 1990 ; Sieweke et al, 1998 ; Posada et al, 2000 ; Kühl et al, 2003 ; Zhan et al, 2005 ; Russell and Garrett-Sinha, 2010 ; Cheng et al, 2011 ; Johansson et al, 2011 ; Tanaka-Nakanishi et al, 2014 ; Okuyama et al, 2018 ). The in-vitro study confirmed that miR-221/-222 inhibited inflammation through those IRF2, CXCL12 and TOX in CVB3 infection (Corsten et al, 2015 ).…”
Section: The Role Of Mirnas In Cvb3-induced Vmcmentioning
confidence: 99%
“…Corsten et al found that CVB3 infection promoted the miR-221/-222 expression in cardiac tissue. Further study demonstrated that miR-221/-222 could inhibit ETS1/2, interferon regulatory factor 2 (IRF2), Bcl-2-like protein 11 (BCL2L11), Thymocyte selection-associated high-mobility group box (TOX), BCL-2-modifying factor (BMF), and CXC chemokine ligand 12 (CXCL12) As we all know, those target genes are important in viral replication and inflammation (Welsh, 1986 ; Bosselut et al, 1990 ; Sieweke et al, 1998 ; Posada et al, 2000 ; Kühl et al, 2003 ; Zhan et al, 2005 ; Russell and Garrett-Sinha, 2010 ; Cheng et al, 2011 ; Johansson et al, 2011 ; Tanaka-Nakanishi et al, 2014 ; Okuyama et al, 2018 ). The in-vitro study confirmed that miR-221/-222 inhibited inflammation through those IRF2, CXCL12 and TOX in CVB3 infection (Corsten et al, 2015 ).…”
Section: The Role Of Mirnas In Cvb3-induced Vmcmentioning
confidence: 99%
“…In fact, sociodemographic data show the social inequalities associated with the high risk of HPV infection leading to cervical cancer, as the virus is more prevalent in public health facilities than in private clinics [ 25 ]. In this context, the lack of knowledge about HPV, as well as its prevention and transmission, is a factor that should be considered in women with less education [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, CXCL12 expression, absent in healthy epithelia, was observed in HPV skin or mucosal lesions [124], suggesting that HPV oncogenes can alter the expression of the chemokine and its receptors CXCR4 and ACKR3 as they do in cultured keratinocytes [125]. Then, expression of the WHIM-associated genetic variant of CXCR4 is capable of biasing the HPV life cycle toward an oncogenic program, as demonstrated in three dimensional (3D) organotypic epithelial cultures [126] in support of its role as a susceptibility co-factor for HPV-induced pathogenesis, as proposed also for genetic variants of CXCL12 [127]. Second, mice harboring WHIM-associated Cxcr4 GOF mutation models the panleukopenia reported in patients [128] in support of critical functions endowed by CXCR4 in immune-hematological processes, including homeostatic immunity, driven by a network of skin-resident immune cells [129].…”
mentioning
confidence: 85%